Numerical simulation of the heat penetration in two-plate arc welding - Payares, C.; Rojas-Solorzano, L.; Viggiani, P. (Conference: h International Congress of Numerical Methods in Engeering and Applied Science (CIMENICS 2000), At Puerto La Cruz, Venezuela, Volume: 5, 2000)
A mathematical model and numerical simulation of the three-dimensional and transient metal arc-welding process is presented. The heat source is considered as spatially distributed following a centered Gaussian bell, while the substract material (Al 6063) is assumed homogeneous and isotropic with temperature-dependent thermal properties. Radiation and convection are also calculated through an empirical temperature dependent correlation. Phase-change phenomenon is included as a discontinuity in the material specific heat. Calculations were performed by using a finite volume code (CFX4.2TM). Computed heat penetration and weld metal area are found to be in good agreement with experimental data.
Keywords: Research Subject Categories::TECHNOLOGY::Engineering mechanics; mechanical engineering